DECONSTRUCTING ACADEMIC BOUNDARIES: A MULTIDISCIPLINARY COMPARATIVE ANALYSIS OF ISLAMIC EDUCATION MANAGEMENT AND GENERAL EDUCATION MANAGEMENT - Usep Ismail; Ahmad Sobirin; Muhamad Rouful Hakim; Deding Ishak; Ahmad Sukandar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This multidisciplinary comparative study examines the academic boundaries between Islamic educational management and general educational management, exploring their philosophical foundations, methodological approaches, and practical implications. Through systematic analysis of 189 scholarly works, this research employs a comparative multidisciplinary framework to deconstruct traditional disciplinary boundaries and identify convergence and divergence points between these two management systems. The findings reveal that while both systems share fundamental management principles planning, organizing, actuating, and controlling they diverge significantly in their epistemological foundations, value systems, and ultimate educational objectives. Islamic educational management integrates divine revelation (Al-Qur'an and Hadith) with management science, emphasizing spiritual development alongside cognitive achievement, whereas general educational management operates within secular, empiricist frameworks prioritizing vocational skills and economic productivity. However, emerging trends indicate potential for integration through shared concerns for holistic human development, quality improvement, and ethical leadership. The study identifies five key areas of substantial difference: educational purpose, philosophical foundations, curriculum management, student development approaches, and institutional governance. This research contributes to ongoing discourse on educational integration by proposing a multilayered model that respects distinctive characteristics while fostering interdisciplinary dialogue. The implications extend to policy development, curriculum design, and leadership training in diverse educational contexts, particularly in pluralistic societies managing both Islamic and secular educational institutions.